La détermination du prix par un tiers en droit française (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Price determination By a third partyThe civil law legislator for the sale contract requires that the place of the contract be determined and specified, which means that the elements of the place, such as the sale and the price, must be determined. Failure to include the price would undermine the entity of the contract due to a defect in the corner of the shop.. In order to avoid the foregoing, the legislator stipulated that: If the two contracting parties did not specify the price of the thing sold, the sale took place at the price on which the transaction took place between them. Adopting another price. Estimating the price may be limited to the bases according to which it is determined later.The legislator also permitted agreement to authorize a third party to determine the price. If this party did not specify the price for any reason whatsoever, the market price on the day of sale must be adopted. If that was not possible, the competent court determined the price. The aim of this research was to focus on the role of the third party in determining the price and to clarify the nature of its role and the limits of its powers and responsibility for the extent of carrying out its mission. In the body of the research, we distinguished between the role of the expert, the role of the arbiter, and the role of the third party in determining the price or consideration in general, and we concluded that he is considered a representative and joint agent of the two contracting parties.Then we moved on to discuss the mechanism of the third party’s intervention in terms of its identification and powers. Finally, the research dealt with the effects of the third party’s intervention on the contract, the binding force of the effect of the intervention on the parties, and finally the controls established by the French jurisprudence and judiciary, which limit the binding force of the effect of the intervention in the event that the third party commits a normal or professional error. significant while estimating the return.